How positive childhood experiences foster college students’ adjustment: the role of sibling number and self-esteem - Li, Juan; Zhang, Xiumei; Chang, Siqi; Zhang, Can; Wang, Wenzhuang (Frontiers in Psychology, 2024)
Introduction In recent years, growing concern has emerged regarding the mental health and well-being of college students who confront numerous challenges and transitions during their higher education journey. This research aims to investigate the influence of positive childhood experiences on the adaptability of college students and the underlying mechanisms. Methods A cross-sectional survey was conducted with 5,787 college students from Chinese universities. Participants completed an online questionnaire assessing positive childhood experiences, self-esteem, the number of siblings, and China college students’ adjustment. Results The results revealed that positive childhood experiences positively predicted the adjustment of China college students, with self-esteem playing a mediating role in this positive effect. Moreover, siblings played an antagonistic moderating role in the positive effect of positive childhood experiences on China college students’ adjustment. Discussion It is recommended to enhance positive childhood experiences, improve self-esteem, and provide additional care and support to students from multi-sibling families to enhance China college students’ adjustment.